Efficacy, immunogenicity, and safety of an oral influenza vaccine: a placebo-controlled and active-controlled phase 2 human challenge study. Issue 4 (April 2020) - Liebowitz, David; Gottlieb, Keith; Kolhatkar, Nikita S; Garg, Shaily J; Asher, Jason M; Nazareno, Jonathan; Kim, Kenneth; McIlwain, David R; Tucker, Sean N
Summary: Background: Influenza is an important public health problem and existing vaccines are not completely protective. New vaccines that protect by alternative mechanisms are needed to improve efficacy of influenza vaccines. In 2015, we did a phase 1 trial of an oral influenza vaccine, VXA-A1.1. A favourable safety profile and robust immunogenicity results in that trial supported progression of the vaccine to the current phase 2 trial. The aim of this study was to evaluate efficacy of the vaccine in a human influenza challenge model. Methods: We did a single-site, placebo-controlled and active-controlled, phase 2 study at WCCT Global, Costa Mesa, CA, USA. Eligible individuals had an initial A/California/H1N1 haemagglutination inhibition titre of less than 20 and were aged 18–49 years and in good health. Individuals were randomly assigned (2:2:1) to receive a single immunisation of either 10 11 infectious units of VXA-A1.1 (a monovalent tablet vaccine) orally, a full human dose of quadrivalent inactivated influenza vaccine (IIV) via intramuscular injection, or matched placebo. Randomisation was done by computer-generated assignments with block size of five. An unmasked pharmacist provided the appropriate vaccines and placebos to the administrating nurse. Individuals receiving the treatments, investigators, and staff were all masked to group assignments. 90 days after immunisation, individuals without clinically significant symptoms or signs of influenza, an oral temperature of higher than 37·9°C, a positive result for respiratory viral shedding on a Biofire test, and any investigator-assessed contraindications were challenged intranasally with 0·5 mL wild-type A/CA/like(H1N1)pdm09 influenza virus. The primary outcomes were safety, which was assessed in all immunised participants through 365 days, and influenza-positive illness after viral challenge, which was assessed in individuals that received the viral challenge and the required number of assessments post viral challenge. This trial is registered with ClinicalTrials.gov, number NCT02918006 . Results: Between Aug 31, 2016, and Jan 23, 2017, 374 individuals were assessed for eligibility, of whom 179 were randomly assigned to receive either VXA-A1.1 (n=71 [one individual did not provide a diary card, thus the solicited events were assessed in 70 individuals]), IIV (n=72), or placebo (n=36). Between Dec 2, 2016, and April 26, 2017, 143 eligible individuals (58 in the VXA-A1.1 group, 54 in the IIV group, and 31 in the placebo group) were challenged with influenza virus. VXA-A1.1 was well tolerated with no serious or medically significant adverse events. The most prevalent solicited adverse events for each of the treatment groups after immunisation were headache in the VXA-A1.1 (in five [7%] of 70 participants) and placebo (in seven [19%] of 36 participants) groups and tenderness at injection site in the IIV group (in 19 [26%] of 72 participants) Influenza-positive illness after challenge was detected in 17 (29%) of 58 individuals in the VXA-A1.1 group, 19 (35%) of 54 in the IIV group, and 15 (48%) of 31 in the placebo group. Interpretation: Orally administered VXA-A1.1 was well tolerated and generated protective immunity against virus shedding, similar to a licensed intramuscular IIV. These results represent a major step forward in developing a safe and effective oral influenza vaccine. Funding: Department of Health and Human Services, Office of the Assistant Secretary for Preparedness and Response, and Biomedical Advanced Research and Development Authority.